Bio-safety of Helicoverpa-resistant transgenic chickpea with Bacillus thuringiensis genes in the environment - SHARMA, H C; DHILLON, M K (The Indian Journal of Agricultural Sciences, 2018)
With the advent of recombinant DNA technology, it has become possible to clone and insert genes into the crop plants to confer resistance to insect pests. Genes conferring resistance to insect pests have been inserted into several crops, and efforts are underway to develop transgenic chickpea with resistance to pod borer, Helicoverpa armigera(Hubner) – which causes an estimated loss of over 500 million annually. However, concerns have been raised regarding the impact of genetically engineered plants on the non-target organisms, gene flow, and biosafety of the food derived from genetically engineered plants. There is no issue related to gene flow involving transgenic chickpea as most of the studies have indicated little or <1% pollen flow to the neighboring plants. The effects of transgenic plants on the activity and abundance of natural enemies vary across crops, and the insect species involved. In general, there are no major adverse effects of genetically modified insect-resistant crops on the generalist predators such as Cheilomenes sexmaculatus, Coccinella septempunctata, and Chrysoperla carnea, while some adverse effects have been observed on the host specific parasitoids such as Campoletis chlorideae, which are largely due to early mortality of the host larvae or poor nutritional quality of the host, rather than direct toxicity of the transgene products to the natural enemies. Wherever the transgenic crops have shown adverse effects on the natural enemies, these effects may still be far lower than those of the broad-spectrum pesticides commonly used for pest management. While no specific studies have been carried out on the biosafety of food derived from transgenic chickpea due to unavailability of events with optimum gene expression for controlling H. armigera, there is enough information on the acute and chronic toxicity of Bt Cry proteins (Cry1Ab, Cry1Ac, and CryIIa), which have also been deployed in commercial transgenic maize and cotton. The issue of biosafety of the food derived from chickpea could also be addressed based on the principle of nutritional equivalence as and when the transgenic events are available for testing. Insect-resistant transgenic crops would play a significant role in pest management in future, and lead to a major reduction in insecticide sprays. Production and release of transgenic chickpea could be based on the guidelines laid down by the concerned agencies internationally, and the experience gained with other transgenic crops for improving food security and environment conservation.